Responsivitas Pelayanan DPPPA Dalam Penanganan Kekerasan Seksual Terhadap Perempuan Di Kabupaten Karawang - Tiara Carendra Gandih; Lukmanul Hakim; Lolita Deby Mahendra Putri (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2026)
Empowerment and Child Protection (DPPPA) of Karawang Regency in handling cases of sexual violence against women. The study employs a qualitative method with a case study approach. Data were collected through interviews, observation, and documentation. Service responsiveness was analyzed using six indicators proposed by Zeithaml as cited in Hardiyansyah (2018): responsiveness capability, service speed, service accuracy, service attentiveness, timeliness of service, and responsiveness to complaints.The findings show that the indicators of responsiveness capability, service accuracy, service attentiveness, and timeliness of service have been implemented effectively through the application of standard operating procedures, empathetic attitudes of officers, and cross-sectoral coordination. However, service speed remains constrained by limited human resource capacity during periods of increased case volume. In addition, responsiveness to complaints has not been optimal due to insufficient dissemination of complaint and feedback mechanisms, resulting in victims being unaware of available channels to submit criticism and suggestions. These findings indicate the need to strengthen human resource capacity, improve workload distribution, and enhance socialization and proactive communication regarding service and complaint mechanisms to improve the responsiveness of women’s protection services.